Which kinds of work stress are related with which types of depression? Workplace satisfaction and subtypes of depression in rural Australians - Christopher F Sharpley; Vicki Bitsika; Kimaya Sarmukadam; Linda L Agnew (Archives of Depression and Anxiety - Peertechz Publications, 2019)
Although the association between Job Satisfaction (JS) and depression has been reported at a global level, relatively little is known about that relationship in terms of specifi c aspects of JS and subtypes of depression. To investigate this issue, eighty-eight employed participants from rural Australia answered questionnaires about JS and depression, plus background factors such as hours worked at paid employment and at unpaid employment. Data were analysed at total JS and depression score level and also for specifi c JS aspects and four subtypes of depression, as well as specifi c depressive symptoms. There were signifi cant correlations between participants' dissatisfaction with the hours they worked at paid employment and global depression, and also for depressed mood and Somatic depression. Specifi c depressive symptoms related to hours worked included feeling downhearted and blue and having trouble sleeping at night. There was also some evidence of an interaction between participants' dissatisfaction with hours worked and their ability to complete non-paid work responsibilities. Identifi cation of the pathways between specifi c aspects of JS and particular subtypes and symptoms of depression suggests possible interventions that may be focussed upon those depression symptoms and/or differential allocation of work hours within the workplace.